2007
DOI: 10.1071/sh07035
|View full text |Cite
|
Sign up to set email alerts
|

Introducing early medical abortion in Australia: there is a need to update abortion laws

Abstract: Recent changes to Federal Therapeutic Goods Administration legislation have seen the limited introduction of the drug mifepristone to Australia for the purpose of early medical abortion. At the same time it has become evident that both methotrexate and misoprostol, licenced and available for other indications, are being used safely and appropriately for early abortion by Australian medical practitioners. Early medical abortion is widely practiced overseas where its safety and effectiveness are well supported b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…There is nothing irregular about this practice (there is no requirement that doctors report such medical abortions to any authority), but it does mean that the data currently available on the number of abortions performed in Australia, which is largely restricted to surgical abortions, is even more inaccurate than it initially appears. More recently, a sexual health clinic in Cairns, QLD, initiated a public abortion service using methotrexate/ misoprostol and reported good results; this clinic now has AP approval for the use of mifepristone and so has discontinued using methotrexate [9,20].…”
Section: Use Of Methotrexate For Medical Abortion In Australiamentioning
confidence: 97%
See 2 more Smart Citations
“…There is nothing irregular about this practice (there is no requirement that doctors report such medical abortions to any authority), but it does mean that the data currently available on the number of abortions performed in Australia, which is largely restricted to surgical abortions, is even more inaccurate than it initially appears. More recently, a sexual health clinic in Cairns, QLD, initiated a public abortion service using methotrexate/ misoprostol and reported good results; this clinic now has AP approval for the use of mifepristone and so has discontinued using methotrexate [9,20].…”
Section: Use Of Methotrexate For Medical Abortion In Australiamentioning
confidence: 97%
“…Mifepristone is, however, available in Australia under the Authorised Prescriber (AP) legislation, according to subsection 19(5) of the Therapeutic Goods Act 1989 [20,103]. This legislation, which has nothing to do with abortion, allows registered medical practitioners to import, and use in their practices, drugs that are recognised and registered for use overseas but are not available in Australia.…”
Section: The Use Of Authorised Prescriber Legislation To Access Mifepmentioning
confidence: 98%
See 1 more Smart Citation
“…Between April 2006 and 30th August 2012, mifepristone could only be obtained by individual practitioners through the TGA's Authorised Prescriber scheme. [15][16][17] On 30th August 2012, the TGA announced that approval to market the drug nationally had been given to MS Health, a company related to the Dr Marie (Marie Stopes International) group of clinics. 18 Also, over the past thirty years, there has been extensive development of techniques for the diagnosis of fetal abnormality, which can provide definitive diagnoses at gestations well before the point of fetal viability outside the uterus.…”
Section: Queensland Criminal Code 1899mentioning
confidence: 99%
“…8 A review of mifepristone use in Cairns Hospital, Australia found that eight of the ten terminations were performed for maternal medical indications. 9 There is no Australian data from a tertiary obstetric setting.…”
Section: Introductionmentioning
confidence: 98%